The neglected role of formal and informal institutions in women's entrepreneurship: a multi-level analysis - Daniela Gimenez-Jimenez; Andrea Calabrò; David Urbano (Journal of International Entrepreneurship, 2020)
This article draws upon institutional theory to investigate whether and to what extent informal institutions (masculinity, power distance, individualism, and indulgence) affect the relationship between formal institutions (the public expenditure on childcare and the length of parental leave) and the likelihood that women will become entrepreneurs. The main findings show that societies characterized by high masculinity and/or low individualism amplify the relationship between the public expenditure on childcare and the likelihood that women will become entrepreneurs. Instead, high-indulgent societies weaken the negative relationship between the length of parental leave and the likelihood that women will become entrepreneurs. We provide a nuanced picture of women's entrepreneurship by considering the neglected role of informal institutions.
Keywords: J16; J24; M13; L26; 330; Women's entrepreneurship; Female entrepreneurship; Formal institutions; Informal institutions; Institutional theory; Multi-level analysis